Konstruksi kekuasaaan politik melalui program charity show media televisi - Indra Setia Bakti; Khairul Amin (Yogyakarta State University, 2019)
As a newcomer, the Perindo Party seeks to implement a specific strategy in order to compete with other parties that have already existed in the Indonesian political contestation. One of these is charity show programs. The high rating and concern societies watching the lives of poor people in various charity programs show besides creating profits also become a means of political communication. When political actors control the media, it is clear that there are interests also communicated, including the political powers of the funnel to get support from voters. When the Perindo Party is declared, the